Kent State : four dead in Ohio - Backderf, Derf, 1959- (Abrams ComicArts, 2020)
From author Derf Backderf comes the untold story of the Kent State shootings. On May 4, 1970, the Ohio National Guard gunned down unarmed college students protesting the Vietnam War at Kent State University. In a deadly barrage of 67 shots, 4 students were killed and 9 shot and wounded. It was the day America turned guns on its own children - a shocking event burned into our national memory. A few days prior, 10-year-old Derf Backderf saw those same Guardsmen patrolling his nearby hometown, sent in by the governor to crush a trucker strike. Using the journalism skills he employed on 'My Friend Dahmer' and 'Trashed', Backderf has conducted extensive interviews and research to explore the lives of these four young people and the events of those four days in May, when the country seemed on the brink of tearing apart. 'Kent State: Four Dead in Ohio', which will be published in time for the 50th anniversary of the tragedy, is a moving and troubling story about the bitter price of dissent-as relevant today as it was in 1970.